2013
DOI: 10.4049/jimmunol.1202996
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Potentiates Mesenchymal Stem Cell–Induced IL-10+IFN-γ+CD4+ Regulatory T Cells To Control Transplant Arteriosclerosis

Abstract: Mesenchymal stem cells (MSCs) are known for their immunomodulatory functions. We previously demonstrated that bone marrow–derived MSCs effectively control transplant arteriosclerosis (TA) by enhancing IL-10+ and IFN-γ+ cells. The objective of this study is to elucidate the mechanism by which MSCs induce IL-10+IFN-γ+CD4+ regulatory T type 1 (TR1)–like cells. In an MLR system using porcine PBMCs, MSC-induced IL-10+IFN-γ+CD4+ cells, which confer resistance to allogeneic proliferation in an IL-10–dependent manner,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 46 publications
4
79
0
2
Order By: Relevance
“…Induction of regulatory T cells is another indirect mechanism for immunoregulation explored by MSCs. IDO expression is responsible for induction of IL-10+IFNγ+CD4+ regulatory T type 1 [T(R)1]-like cells by MSCs [183] . Neutralization of IDO is also a reason for Treg reduction [184] .…”
Section: Indoleamine-23-dioxygenasementioning
confidence: 99%
See 3 more Smart Citations
“…Induction of regulatory T cells is another indirect mechanism for immunoregulation explored by MSCs. IDO expression is responsible for induction of IL-10+IFNγ+CD4+ regulatory T type 1 [T(R)1]-like cells by MSCs [183] . Neutralization of IDO is also a reason for Treg reduction [184] .…”
Section: Indoleamine-23-dioxygenasementioning
confidence: 99%
“…Together with IDO, PGE2 is another major effector molecule responsible for immunoregulatory competence of MSCs [183] . MSCs constitutively produce detectable levels of PGE2 [44,227,228] .…”
Section: Prostaglandin E2mentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are also conflicting reports on this subject. Some authors have suggested that MSCs promote the generation of CD4 + CD25 + forkhead box P3 (Foxp3) or CD4 + CD25 high Foxp3 + T-cell populations [7,8,[25][26][27], while others indicate that BMMSCs-induced Tregs populations are not Foxp3 + [4,28]. Apparently, these contradictory findings might be due to the T-cell populations used and the absence or presence of cell contact with BM-MSCs [9].…”
Section: Introductionmentioning
confidence: 99%